Stres kerja dan cyberloafing pada karyawan - Dewi Lawung Wati Tri Wardani; Diah Sofiah; Etik Darul Muslikah (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract The increasing integration of digital technology in the workplace has made internet use indispensable, while simultaneously giving rise to cyberloafing, defined as employees’ use of organizational internet resources for personal purposes during working hours. Job stress has been identified as a potential psychological antecedent of cyberloafing, particularly when perceived job demands exceed individual coping resources. This study examines the relationship between job stress and cyberloafing among employees of the Social Service Office of Surabaya City. This study employed a quantitative correlational design was employed, involving 112 employees as participants. Data were collected using validated job stress and cyberloafing scales with a five-point Likert format. Given the non-normal distribution of the data, Spearman’s Rank correlation was applied for hypothesis testing. The results revealed a positive and highly significant association between job stress and cyberloafing (rs = 0.602, p < 0.01). These findings are consistent with the Transactional Model of Stress, which suggests that individuals may engage in maladaptive coping strategies when confronted with excessive work demands. In conclusion, job stress constitutes a significant factor associated with cyberloafing behavior among employees in governmental institutions, highlighting the importance of effective stress management and clear internet usage policies Abstrak Perkembangan teknologi digital menjadikan internet sebagai bagian penting dalam aktivitas kerja, namun juga memunculkan perilaku cyberloafing, yaitu penggunaan internet organisasi untuk kepentingan pribadi selama jam kerja. Stres kerja diduga berperan dalam mendorong munculnya perilaku tersebut sebagai bentuk coping maladaptif ketika tuntutan pekerjaan melebihi kemampuan individu. Penelitian ini bertujuan untuk mengetahui hubungan antara stres kerja dan cyberloafing pada karyawan Dinas Sosial Kota Surabaya. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Subjek penelitian berjumlah 112 karyawan. Data dikumpulkan menggunakan skala stres kerja dan skala cyberloafing dengan format Likert lima poin, kemudian dianalisis menggunakan korelasi Spearman Rank karena data tidak berdistribusi normal. Hasil penelitian menunjukkan adanya hubungan positif yang sangat signifikan antara stres kerja dan cyberloafing (rs = 0,602; p < 0,01). Temuan ini mendukung Transactional Model of Stress yang menjelaskan bahwa stres kerja dapat memicu strategi coping maladaptif. Penelitian ini menyimpulkan bahwa stres kerja berperan penting dalam meningkatnya perilaku cyberloafing pada karyawan instansi pemerintahan.